2014
DOI: 10.1016/j.schres.2014.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of the combination of galantamine and memantine to improve cognition in schizophrenia

Abstract: The Measurement and Treatment Research to Improve Cognition in Schizophrenia (MATRICS) and Treatment Units for Research on Neurocognition and Schizophrenia projects were designed to facilitate the development of new drugs for the treatment of cognitive impairments in people with schizophrenia. The MATRICS project identified three drug mechanisms of particular interest: dopaminergic, cholinergic, and glutamatergic. As a group, while people with schizophrenia have moderate cognitive impairment, it is the best pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 73 publications
0
52
1
1
Order By: Relevance
“…The KYNA hypothesis in schizophrenia is well documented [98, 99]. The galantamine-memantine combination may be effective for CIAS with KYNA as a biomarker to detect the severity of cognitive impairments and monitor progress (target engagement) with treatment [100, 101]. There is also evidence from a small open-label study that this combination may be effective for CIAS with concurrent improvement in KP metabolite concentrations [102].…”
Section: Kynurenine Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The KYNA hypothesis in schizophrenia is well documented [98, 99]. The galantamine-memantine combination may be effective for CIAS with KYNA as a biomarker to detect the severity of cognitive impairments and monitor progress (target engagement) with treatment [100, 101]. There is also evidence from a small open-label study that this combination may be effective for CIAS with concurrent improvement in KP metabolite concentrations [102].…”
Section: Kynurenine Pathwaymentioning
confidence: 99%
“…Given that there are no available treatments for CIAS and negative symptoms, testing of quintuple hypotheses (dopamine, nicotinic-cholinergic, glutamatergic/NMDA, GABA, and KYNA) is a “low-risk high-gain” approach that could significantly advance our field. Multitarget drug discovery may play a role in the treatment of complex diseases [161] including, but not limited to, schizophrenia [100, 162]. …”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…For example Atri et al have shown that combination treatment with memantine added to donepezil in patients with moderate to severe Alzheimer's disease is associated with significant benefits in reducing 24 weeks decline in cognition, function and global status (Atri et al, 2013). In another study, the combination of galantamine and memantine was effective in schizophrenia in order to increase the selective cognition enhancement produced by either medication alone (Koola et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The galantamine-memantine combination may be effective for cognitive impairments in schizophrenia [37, 41, 43-46]. Excess kynurenic acid (KYNA) may be associated with cognitive impairments in schizophrenia [47].…”
mentioning
confidence: 99%
“…KYNA is an antagonist of the α-7nACh and NMDA receptors. The galantamine-memantine combination through the α-7nACh and NMDA receptors may counteract the effects of KYNA, thereby improving cognition [37, 41, 43-46]. Although the KYNA hypothesis is well established in schizophrenia [48, 49], there is no evidence of abnormal kynurenine pathway (KP) metabolites in CHR due to a lack of studies.…”
mentioning
confidence: 99%